The reality of the moral climate and its relationship to the decision-making of boxing referees from the standpoint of coaches - Layla Abdulameer Ibrahim; Mohammed Qusay M; Hussein Khamees Hussein (Eximia, 2024)
The purpose of this paper is to identifying the relationship between the moral climate and the decision-making of boxing referees from the standpoint of the coaches, and the research problem lies through the work of the researchers in training and managing the teams. It was noted that the role of the referees is one of the most important roles played by the workers to achieve the objectives of the federation, and that the moral climate that prevails among the administrative body the union and the referees on the one hand and between the referees and coaches on the other hand are among the factors of the success of everyone’s work and the survival and strengthening of confidence in their work and thus the continuity of success and production and the achievement of goals, hence the desire to conduct this study, and the researchers used the descriptive approach in the manner of correlations to suit it with the nature of the research problem, The study population consisted of (160) coaches and referees in the Boxing Federation. As for the research sample, it was divided into a sample of adapting the moral climate scale, which consisted of (70) judges. As for the building sample for the decision-making scale, it consisted of (90) coaches. The standards (moral climate) were modified and built. for the administrative body, decision-making for the referees), the measures were applied to the research sample in order to extract the results of the research and achieve the goal of the research, which is to identify the relationship between the moral climate and decision-making for boxing referees from the point of view of the coaches and it was found that they are at an above average level in the moral climate and decision-making as well That there is a direct relationship between the two research variables (moral climate and decision-making), that is, the greater the moral climate, the greater the decision-making.